Is There an Increased Risk of Intra-Abdominal Abscesses After Laparoscopic Appendectomy? Laparoscopic Versus Open Appendectomy: A Single-Institution Experience - Almuhaisen, Mays Ziad; Alimoglu, Orhan; Ayoub, RM; Alsunna, Raad; Qudah, Mohammad; Elmuhtaseb, MS (Jordan Medical Journal, 2023)
Background: Acute appendicitis is the most common cause of acute abdomen. Currently, larger numbers of appendectomies are being performed laparoscopically. The aim of this study was to compare laparoscopic appendectomies to open surgery in terms of intra- and post-operative complications, including the risk of intra-abdominal abscess formation, operative time, time of initiating oral diet, and the length of hospital stay in our institution. Methods: The study group of 283 patients having undergone appendectomies between January 2013 and Jan 2016 was divided into two subgroups as ‘open’ and ‘laparoscopic’. The data regarding the surgical outcomes of these groups were evaluated retrospectively and statistically analyzed. Results: In terms of postoperative complications, intra-abdominal abscesses were found to be higher in the laparoscopic group (p=.045). On the other hand, surgical site infection (SSI) rates were found to be higher in the open group (but did not reach statistical significance). Operative time was affected by the surgeon’s expertise and was found to be shorter in the laparoscopic group (p<0.05). The time of initiating oral diet was sooner in the laparoscopic group compared to the open group (p=0.043), and the overall length of hospital stay was shorter in the laparoscopic group (p=0.0001). Conclusions: Laparoscopic appendectomy is associated with early return to a normal diet, fewer wound complications, and a shorter hospital stay, but also with a slightly higher rate of intra-abdominal abscesses. Notably, it is now the standard method of acute appendicitis management in some centers.